The woman who died a lot [large type] : now with 50% added subplot - Fforde, Jasper (Fforde, Jasper. Thursday Next., 2013)
The Bookworld's leading enforcement officer, Thursday Next, has been forced into semiretirement following an assassination attempt. When Thursday's former SpecOps division is reinstated, she assumes she's the obvious choice to lead the Literary Detectives. But our banged-up heroine is no spring chicken, and her old boss has a cushier job in mind for her: chief librarian of the Swindon All-You- Can-Eat at Fatso's Drink Not Included Library. But where Thursday goes, trouble follows . . . (Bestseller)